Analisis Produktivitas Waktu Kerja Alat Berat Pada Pembangunan Lanjutan Reklamasi Dan Jalan Kawasan Kayu Merah-Kalumata - M. Irsan Sangadji; Edward Rizki Ahadian; M Darwis (Journal of Science and Engineering, 2021)
The development of the construction world has resulted in the increasing need for heavy equipment for each project. Heavy equipment is a vital resource in a construction project. However, the costs required to procure heavy equipment are not cheap. Therefore, the choice of heavy equipment has a big influence on the efficiency and profitability of construction work. Productivity is used as a guide in determining the duration of each job and the number of heavy equipment to be treated. This research was conducted by observing the field to obtain the time needed by each heavy equipment in the reclamation work which then carried out the calculation of productivity. The results of the research are that the trailer/trailer truck has a productivity of 60.614 minutes, the excavator has a productivity of 21 m³/hour, the roller vibrator has a productivity of 155.625 m³/hour, the wheel loader has a productivity of 91.098 m³ hour, the water tanker has a productivity of 14.229 m³/hour, the motor grader has a productivity is 942,880 m²/hour, and the dump truck has a productivity of 26,981 m³/hour, then after analyzing the productivity of heavy equipment the next stage is calculating the time efficiency that occurs in each work item, and the mobilization work takes 17 days or less than the expected time. it has been planned in the contract document that is 28 days, in the usual piling work from the excavation source it will take 247 days or less than the time planned in the contract document which is 287 days.